Verstek dalam Perkara Perceraian di Pengadilan Agama dan Implikasinya terhadap Putusan - Hafizah Salsabilah Manik; Maria Rosalina; Shakila Aminah Pulungan; Siti Zahra Hsb (Lembaga Yasin AlSys, 2026)
Divorce cases in the Religious Courts require a balance between the efficiency of case resolution and the protection of the defendant’s rights, especially when a decision is rendered in the defendant’s absence through the verstek mechanism. This study aims to analyze the mechanism for applying verstek decisions in divorce cases in the Religious Courts and to formulate effective legal protection measures for defendants through the verzet mechanism. This study used a normative legal method with a prescriptive doctrinal approach through the examination of primary legal materials, such as HIR and RBg, as well as other relevant legal literature. The results show that verstek decisions are an important instrument for preventing stagnation in the judicial process due to the defendant’s passive attitude, but judges still have a judicial obligation to conduct ex officio examination to ensure that the claim is well-founded and does not violate rights. In divorce cases, the application of verstek has specific characteristics because judges bear a moral burden to view divorce as an ultimum remedium. As a balancing mechanism, verzet functions as an instrument of legal protection that provides defendants with a second opportunity to defend themselves and refute the plaintiff’s arguments through adversarial examination. The conclusion of this study affirms that the regulation of verstek and verzet represents a synthesis between the need for judicial efficiency and respect for substantive justice. The implications of this study indicate the importance of applying the principle of judicial prudence in divorce cases and the need for further socio-legal studies to assess the effectiveness of implementing such decisions in judicial practice across various regions.